2012
DOI: 10.1167/iovs.11-9234
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Intraocular Lens Differentiation Using Defocus Curves

Abstract: PURPOSE. To determine the most appropriate analysis technique for the differentiation of multifocal intraocular lens (MIOL) designs by using defocus curve assessment of visual capability.METHODS. Four groups of 15 subjects were implanted bilaterally with either monofocal intraocular lenses, refractive MIOLs, diffractive MIOLs, or a combination of refractive and diffractive MIOLs. Defocus curves between À5.0 D and þ1.5 D were evaluated by using an absolute and relative depth-of-focus method, the direct comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 20 publications
5
70
2
3
Order By: Relevance
“…There was an interaction between lens types and acuity at different levels of defocus, showing that the lens types worked differently from one another, with monovision and the Biofinity design generally outperforming the OASYS and Air Optix Aqua designs. However, similar to the findings of Gupta et al, 3 the near-vision peak, commonly observed in multifocal intraocular lens designs, 37 was not evident in the present study. This is likely to occur because of the difficulty in constructing sharp transitions in lens molds leading to intermediate distance focused transitions even in the less aspheric designs.…”
Section: Discussionsupporting
confidence: 88%
“…There was an interaction between lens types and acuity at different levels of defocus, showing that the lens types worked differently from one another, with monovision and the Biofinity design generally outperforming the OASYS and Air Optix Aqua designs. However, similar to the findings of Gupta et al, 3 the near-vision peak, commonly observed in multifocal intraocular lens designs, 37 was not evident in the present study. This is likely to occur because of the difficulty in constructing sharp transitions in lens molds leading to intermediate distance focused transitions even in the less aspheric designs.…”
Section: Discussionsupporting
confidence: 88%
“…A recent trend is the combined implantation of different multifocal IOLs in each eye. Studies showed that combined implantation of refractive and diffractive multifocal IOLs provides better near vision than bilateral implantation of the same IOL due to binocular summation 24 25. Accordingly, combined implantation of the ReSTOR +2.5 D and other near-dominant diffractive IOL may be a useful option for correcting presbyopia.…”
Section: Discussionmentioning
confidence: 99%
“…Buckhurst et al. () reported that patients who underwent combined implantation of refractive and diffractive MIOLs have binocular near and intermediate vision comparable to that of patients who underwent bilateral implantation of the same refractive or diffractive MIOL. No studies to date, however, have examined binocular visual function with mix and match implantation of diffractive MIOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using a stricter study design also showed that combined implantation of refractive and diffractive MIOLs provided better near vision than bilateral implantation of the same refractive IOL (Buckhurst et al. ; Lin et al. ).…”
Section: Introductionmentioning
confidence: 99%